Implementation Of Strategic Agility Planning At Nafalu Kopi Gondanglegi: A Micro Business In Malang Regency East Java Indonesia - Amelia Setyawati; Marisa Sugangga; Adelia Rahma; Dieva Zahrotu Anfi; Intan Permata Sari (International Journal of Economics and Management Research, 2023)
This study aims to examine the application of Strategic Agility Planning in Nafalu Kopi, a micro business located in Gondanglegi, Malang Regency, East Java, Indonesia. Using a qualitative approach through case studies, this research focuses on evaluating the implementation of strategic agile planning in the context of microbusiness. The selection of Nafalu Kopi as the subject of research was based on its uniqueness and potential as a micro enterprise in the region. This study tries to reveal how Nafalu Kopi applies the principles of strategic agility in its business operations, looking at aspects such as adaptation to market changes, innovation in service, and flexibility in business strategy. This research is expected to provide insight into best practices and challenges in implementing strategic agility planning in the micro enterprise sector. The results of this study intend to provide strategic recommendations for the development of similar micro enterprises, as well as contribute to the academic literature on the application of agile business strategies in the micro business environment.